The Duality of Global Airports: A Study on the Divergence Between Passenger Nodes and Cargo Hubs - Yacoubian, Leandro Jorge; Merdinian, Kevin; Viana, Márcia de Negreiros; Ketenchian, Grigor Sahak; García, Daniel Santo Padilla; Carvalho, George Harrison Ferreira de (Revista JRG de Estudos Acadêmicos, 2025)
This study analyzes the divergence between the roles of global airports as passenger nodes and cargo hubs. Although airports are crucial components of global transportation networks, leadership in passenger connectivity does not guarantee dominance in cargo operations. The research employs a comparative framework integrating three key data sources: the 2024 Air Connectivity Index (ACI), 2024 Freight & Mail volumes from the Airports Council International (ACI), and the 2023 Logistics Performance Index (LPI) Infrastructure sub-index from the World Bank. A Spearman correlation is used to examine the association between connectivity and the quality of national logistics infrastructure across 20 European airports. The results reveal a notable specialization among airports. European airports such as Frankfurt (FRA) and Paris (CDG) present a balanced performance. The correlation analysis found no statistically significant association between the ACI Connectivity Index and the LPI ranking (ρ = -0.235, p = 0.318), suggesting that high-quality national logistics performance does not directly translate into greater air passenger connectivity. The study concludes that air cargo competitiveness is a multidimensional outcome, significantly influenced by institutional frameworks and specific policies beyond physical infrastructure. It is argued that airports must adopt integrated strategies that combine infrastructure, institutional efficiency, and targeted cargo policies rather than relying solely on connectivity as a measure of success.